2016
DOI: 10.1007/s40891-016-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of Soil Slopes in Shaking Table Tests: Effect of Type and Quantity of Reinforcement

Abstract: To study the effect of reinforcement type and quantity on the response of model slopes in this study, a series of shaking table tests were carried out on model slopes reinforced with different quantities of geotextile and geogrid. Model slopes were constructed to an angle of 45°using poorly graded sand. Acceleration of base shaking and shaking frequency were varied in different tests. The response of model soil slopes is compared in terms of the acceleration amplifications and horizontal displacements of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This indicates that the landslide presents obvious amplification effect on input seismic waves. Moreover, the PGA amplification factor increases along the height of landslide, and it reaches a maximum at the top of the landslide, which is similar to the observations in other slopes studied by previous researchers (Meunier et al 2008;Fan et al 2016;Srilatha et al 2016).…”
Section: Acceleration Response Analysissupporting
confidence: 89%
“…This indicates that the landslide presents obvious amplification effect on input seismic waves. Moreover, the PGA amplification factor increases along the height of landslide, and it reaches a maximum at the top of the landslide, which is similar to the observations in other slopes studied by previous researchers (Meunier et al 2008;Fan et al 2016;Srilatha et al 2016).…”
Section: Acceleration Response Analysissupporting
confidence: 89%
“…Those researchers also discussed the influence of the reinforcement material arrangement on the model response. However, compared with reinforced walls, studies on the dynamic responses of reinforced slopes with gentle slopes are relatively limited, particularly studies on gravel slopes (Lin et al, 2015;Edinç liler and Toksoy 2016;Srilatha et al, 2016;Xu and Yang 2019;Wang et al, 2019). Meanwhile, for reinforced slopes, most studies have focused on the reinforcing effect of geotextile.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the displacement increased proportionately with the seismic frequency, whereas frequency had little effect on the acceleration amplifications. Furthermore, Srilatha et al (2016) investigated the effects of different reinforcement materials (geotextiles and geogrids) on the response of a model slope. Their results showed that a geotextile-reinforced slope better reduced lateral deformation compared to a geogrid-reinforced slope, and that varying the reinforcement quantity had no effect on the acceleration amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars believe that it is necessary to reinforce the slope mentioned above. eory and experiments have been developing very quickly for the reinforced slope under dynamical response [17][18][19][20][21]. For an unstable slope with the potential sliding surface (structural surface), prestressed anchor cable is usually adopted.…”
Section: Introductionmentioning
confidence: 99%